METAFORA HEWAN DALAM PERIBAHASA LAMPUNG - Kastri, Evi Maha (Jurnal Kata : Bahasa, Sastra, dan Pembelajarannya, 2022)
As a society that knows culture, the people of Lampung have a 'proverb' sasikun as one of the cultural treasures. In fact, the proverb is still used in everyday life by indigenous peoples. One of the proverbs used is a proverb that contains animal metaphors. This study aims to find out the animal metaphor used in the proverbial Lampung. This research uses a qualitative descriptive method with a free listening technique. The research data is sourced from a book collection of proverbs entitled Sasikun Kicik Lampung: Proverbs of the Lampung People. The analysis of the form of conceptual meaning of animal metaphors in Lampung proverbs refers to the theory of Lakoff and Johnson. The results showed that there were 39 animal metaphorical proverbs which included 1) poultry animal metaphors, 2) mammalian animal metaphors, 3) reptile animal metaphors, 4) fish animal metaphors, and 5) insect animal metaphors. Sebagai masyarakat yang mengenal budaya, masyarakat Lampung memiliki sasikun ‘peribahasa’ sebagai salah satu kekayaan budaya. Bahkan, peribahasa itu tetap dipergunakan dalam kehidupan sehari-hari oleh masyarakat adat. Salah satu peribahasa yang digunakan ialah peribahasa yang mengandung metafora hewan. Penelitian ini bertujuan untuk mengetahui metafora hewan yang digunakan dalam peribahasa Lampung. Penelitian ini menggunakan metode deskriptif kualitatif dengan teknik simak bebas libat cakap. Data penelitian bersumber dari buku kumpulan peribahasa yang berjudul Sasikun Kicik Lampung: Peribahasa Orang Lampung karya (Perbasa, 1989). Analisis bentuk makna konseptual metafora hewan dalam peribahasa Lampung mengacu pada teori Lakoff dan Johnson. Hasil penelitian menunjukkan terdapat 39 peribahasa metafora hewan yang meliputi 1) metafora hewan unggas, 2) metafora hewan mamalia, 3) metafora hewan reptil, 4) metafora hewan ikan, dan 5) metafora hewan serangga.Keywords: proverbs, animal metaphors